Hypertensive emergency due to vasculitis: a case report - Sumant Prabhudesai; Chetna Khemani (Wolters Kluwer Medknow Publications, 2019)
Hypertensive emergencies commonly occur due to an underlying renal or reno-vascular disease. Vasculitis is an uncommon cause. We report a 5 year old boy who presented with hypertension, heart failure and posterior reversible encephalopathy syndrome (PRES). Subsequent evaluation led to the diagnosis of polyarteritis nodosa (PAN). PAN is an uncommon but well known cause of hypertension. However, hypertensive encephalopathy and PRES have been rarely reported in childhood PAN.